Inside Front Cover, Volume 2, Number 1, January 2023. Issue 1 (18th January 2023) - Xu, Bojie; Chen, Xuan; Zhao, He; Zhang, Zhen; Liu, Huan
Abstract : Inside Front Cover : The cover image is based on the Research Article Preparation of nano‐pico droplets using an open fibrous system by Xu et al. This cover image (DOI: 10.1002/dro2.27 ) demonstrates that a macroscopic droplet on a micro‐/nano‐textured copper fiber could be dispersed to a number of tiny droplets by applying and removing a suitable electric potential. The facile strategy offers an innovative open system for continuous preparation of nano‐pico droplets.